Ingenuity and innovation. The catch-fogs as objects-fluids - Yrivarren, Joaquín (2017)
In this essay we discuss the notion of ‘prospective’ and the dilemmas to imagine the future for taking decisions now. For many, daily life follows a short-term horizon (‘events’), meanwhile the ‘prospective’ looks for a new open horizon for actions and projects (‘scenarios’). The matter is, precisely, to articulate ‘events’ and ‘scenarios’, or which is the same, to traslate ingenious projects into long-term innovations. Our broader aim is to describe possible worlds without forgetting ‘events’, as well as to base innovation into resources and learnings steammed from ingenuity. This aim, empirically, implies to analyze ‘data of little future’ and ‘pluri-trends’. For, we present the case of catch-fogs in Villa María del Triunfo (Lima) and describe the transit from its period of trials, its definition as ‘fluid-object’ until its growth as an urban project.